Great Expectations - Dickens, Charles, 1812-1870. (New Delhi, India Rupa Publications India Pvt. Ltd., 2000)
The adventures of an orphaned young man in Victorian England who is given a great deal of money by an unknown benefactor to enable him to live as a gentleman, pursuing a good education and fulfilling great expectations.
Keywords: Orphans -- Fiction; Coming of age -- Fiction; Great Britain -- History -- 19th century -- Fiction; Fiction